Associations Between Resilience, Psychological Well-Being, Work-Related Stress and Covid-19 Fear in Forensic Healthcare Workers Using a Network Analysis - Bogaerts, Stefan; van Woerkom, Marianne; Erbaş, Yasemin; De Caluwé, Elien; Garofalo, Carlo; Frowijn, Iris; Jeandarme, Ingeborg; Masthoff, Erik; Janković, Marija (Frontiers in Psychiatry, 2021)
Forensic healthcare professionals deal with patients with severe psychiatric and behavioral problems that put them at an increased risk of developing work-related stress and burnout. Working with this target group of patients during the Coronavirus disease 2019 (Covid-19) pandemic with far-reaching restrictive measures can negatively affect the psychological well-being of forensic workers. Research suggests that resilience can buffer workplace stress and is positively associated with psychological well-being. However, research on resilience, psychological well-being and work-related stress among forensic healthcare professionals is still lacking. Therefore, in this study, we investigated the interrelations between psychological well-being and resilience on the one hand and work-related stress and Covid-19 fear-related symptoms on the other hand. Self-report data was obtained from 318 healthcare professionals (73.9% women) working in three Forensic Psychiatric Centers (M age=44.20, SD=14.31) and are in direct contact with forensic patients. The data was analyzed using network analysis. Consistent with previous research, the results showed that workplace stress and fear associated with the Covid-19 pandemic can be detrimental to workers’ psychological well-being, while resilience can serve as a protective factor against work-related stress. Last but not least, we identified highly central symptoms, namely tremors due to the fear of the coronavirus and anxiety when other people coughing, which would be the best candidates for future treatment targets. This knowledge can help clinicians optimize interventions to reduce workplace stress and fear due to the pandemic.